Effectiveness of follow‐up reminiscence therapy on autobiographical memory in pathological ageing. (17th September 2015) - Melendez, Juan C.; Torres, Marta; Redondo, Rita; Mayordomo, Teresa; Sales, Alicia
Abstract : The objective is to examine the effects of reminiscence therapy (RT) on total, episodic and semantic autobiographical memory in amnestic mild cognitive impairment (aMCI) and Alzheimer's disease (AD) groups, testing the effects of RT on different stages of autobiographical memory, and its effectiveness at follow‐up. A sample composed of 43 aMCI (27 treatments, 16 controls) and 30 AD (15 treatments, 15 controls) subjects were evaluated with the Autobiographical Memory Interview (AMI) test. The RT consisted of 10 sessions lasting 60 minutes each. Both groups, aMCI and AD, showed significant effects on overall autobiographical memory; aMCI showed significant main effects on episodic and semantic autobiographical memory in the treatment group, increasing scores in both cases. For AD, significant effects were observed on autobiographical episodic memory, showing an increase in the treatment group from Time 1 to follow‐up; semantic memory showed a decrease in the control group from Time 1 to follow‐up. Results show that RT implementation and follow‐up are effective in increasing autobiographical memory in subjects with aMCI and AD.